Social Resources and Strength of Ties: Structural Factors in Occupational Status Attainment - Lin, Nan; Ensel, Walter M.; Vaughn, John C. (American Sociological Review, 1981)
Nan Lin, Walter M. Ensel, John C. Vaughn, Social Resources and Strength of Ties: Structural Factors in Occupational Status Attainment, American Sociological Review, Vol. 46, No. 4 (Aug., 1981), pp. 393-405